Target Corporation : pharmacists acts of conscience and the "plan B" pill - Cox, Joshua L.; Berry, Katherine M.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In September 2005, Rachel Pourchot entered a Target store in Fenton, Missouri, intending to fill prescriptions for Ortho TriCyclen, a common hormonal contraceptive, and for Levonorgestrel, an emergency contraceptive known as the "Plan B" pill. Targets pharmacist, however, told her that he would not fill the prescription for Levonorgestrel on moral and religious grounds. As competitors Walgreens and Wal-Mart made their positions clear on the issue of pharmacists acts of conscience, Target Corporation struggled with an appropriate response that would satisfy the needs of its customers and its employees, while protecting the reputation of the firm at the same time.
Originally published: Cox, J. L., Berry, K. M., & ORourke, J. S. (2006). Target Corporation: Pharmacists acts of conscience and the "Plan B" pill. 06-11. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Target Corporation; Pharmaceutical industry -- Moral and ethical aspects; Levonorgestrel intrauterine contraceptives